Factors influencing awareness and practice on household solid waste management among rural areas residents at Alor Pongsu, Kerian District / Nor Hamimi Mohamad and Mohd Izwan Masngut - Mohamad, Nor Hamimi; Masngut, Mohd Izwan (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Improper household solid waste management may cause various diseases to humans and bad impact on the environment. In addition, the majority of rural areas still practice dig and burn as a common practice of household waste management due to lack of an proper effective waste management system. Descriptive correlational study involving a total of 142 respondents in Alor Pongsu, Kerian district, Perak. Data were collected using face-to-face interview using a set of questionnaires for socio-demography profiles together with awareness and practice level on household solid waste. Data Analysis were done using SPSS for both; descriptive statistics on socio demography and Chi-Square for determining relationship between parameters. Awareness and practice on managing solid waste at home among residents in the study area were at moderate levels. Mean awareness on household solid waste was 6.965 (SD = 3.209) and the mean for practice level was 2.429 (SD = 0.593). Age, marital status, education level, problem in household solid waste management and training on household solid waste management were significantly correlated with awareness level (p<0.001). Meanwhile training on household solid waste management was significantly correlated with practice level on proper household solid waste management among the resident (p < 0.005). Sustainable management of household solid waste practice amongst residents in rural area could be achieved by focusing on awareness and practice elements.